Rethinking the clinical management of volumetric muscle loss in patients with spinal cord injury: Synergy among nutritional supplementation, pharmacotherapy, and rehabilitation. (April 2021) - Invernizzi, Marco; de Sire, Alessandro; Fusco, Nicola
Abstract: Spinal cord injury (SCI) is a condition defining the damage of the spinal cord that leads to musculoskeletal sequelae, including volumetric muscle loss (VML) in a significant proportion of patients. VML occurring after SCI is responsible for delayed recovery, with detrimental consequences in terms of functional outcomes and additional alterations of the muscle tissue. The treatment of muscle alterations in these patients usually relies on nutritional supplementation. However, rehabilitation therapy has a well-recognized role in improving muscle mass and function, even in subjects affected by SCI. Furthermore, novel medical therapies have been recently investigated, with positive results. In this scoping review, we portray the state-of-the-art treatment of muscle modifications after SCI, focusing on the multidisciplinary and multidimensional management of these patients.